Astroparticle projects at the Eastern Colombia region: facilities and instrumentation - Sierra-Porta, David (Scientia et Technica, 2018)
We describe some projects and initiatives for astroparticles physics from basic and application level. Three specialized instruments have been design, built and put into operation for the study of various characteristics and phenomena of cosmic rays. One of detector based on Cherenkov effect consists of three Water Cherenkov Detectors calibrated spatially and temporally, that allow the characterization of secondary cascades of cosmic ray particles. These devices allow to study the original composition and parameters of primary cosmic rays from the secondary particles detected on the ground. A second type of detectors based on scintillation effect are used for specific applications in the characterization of materials and mountainous structures. These detectors allow the counting of incident secondaries particles (muons mainly) while determining their arrival direction. Studing their attenuation in the material medium we can infer composition and density profiles.